2019
DOI: 10.1016/j.nicl.2019.101999
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative susceptibility mapping in atypical Parkinsonisms

Abstract: Background and purposeDifferential diagnosis between Parkinson's disease (PD) and Atypical Parkinsonisms, mainly Progressive Supranuclear Palsy (PSP) and Multiple System Atrophy (MSA), remains challenging. The low sensitivity of macroscopic findings at imaging might limit early diagnosis. The availability of iron-sensitive MR techniques and high magnetic field MR scanners provides new insights in evaluating brain structures in degenerative parkinsonisms. Quantitative Susceptibility Mapping (QSM) allows quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 55 publications
5
68
4
1
Order By: Relevance
“…However, the RN and GP were not capable of differentiating between MSA from IPD patients in our study. Furthermore, the CN has been reported to be have no statistical differences in iron content between PD and AP patients (Han et al, 2013;Sjostrom et al, 2017;Mazzucchi et al, 2019). Similarly, in our present study, the radiomic features extracted from the RN, GP, and CN showed moderate to poor differential diagnostic values.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…However, the RN and GP were not capable of differentiating between MSA from IPD patients in our study. Furthermore, the CN has been reported to be have no statistical differences in iron content between PD and AP patients (Han et al, 2013;Sjostrom et al, 2017;Mazzucchi et al, 2019). Similarly, in our present study, the radiomic features extracted from the RN, GP, and CN showed moderate to poor differential diagnostic values.…”
Section: Discussionsupporting
confidence: 61%
“…Similarly, in our present study, the radiomic features extracted from the RN, GP, and CN showed moderate to poor differential diagnostic values. However, Mazzucchi et al (2019) found that the STN might be useful for differentiating MSA from PD. This discrepancy may be due to the small size of the STN and difficulty in its visualization on SWI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the differential diagnosis between PD and atypical parkinsonism's, QSM techniques allow for more sensitive measures in the nigral and extranigral regions. Mazzucchi et al (32) found that the greatest diagnostic accuracy for PSP was for increased χ values in the RN, subthalamic nucleus (STN), and medial part of the SN, whereas for MSA, it was a significantly higher level of iron deposition in the putamen, reflecting the different patterns of pathological involvement that characterize these diseases (32).…”
Section: Iron-sensitive Imagingmentioning
confidence: 99%
“…Unlike in conventional T1-weighted and T2*-weighted imaging, these two types of substances generate opposite image contrasts in QSM, making it particularly useful in applications where the tissues with opposite properties need to be distinguished, such as between haemorrhages and calcifications (Chen et al, 2013). Additionally, strong correlations were demonstrated in various ex vivo studies between iron concentration in the deep nuclei and magnetic susceptibility (Langkammer et al, 2012;Sun et al, 2015), showing evidence of the quantitative ability of QSM which can find applications on studying, for example, the relationships between iron overload and neurodegenerative diseases, including Parkinson's disease (He et al, 2015;Ide et al, 2015;Langkammer et al, 2016;Mazzucchi et al, 2019;Thomas et al, 2020), Huntington's disease (Chen et al, 2018;, Alzheimer's disease (Acosta-Cabronero et al, 2013;Bulk et al, 2020;Du et al, 2018;Gong et al, 2019;O'Callaghan et al, 2017), and between iron deposition in the brain and ageing (Acosta-Cabronero et al, 2016;Betts et al, 2016;Bilgic et al, 2012;Gong et al, 2015;Keuken et al, 2017;Liu et al, 2016;Persson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%